2018
DOI: 10.1177/1940082918802758
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Human–Wildlife Interactions in a Forest Settlement in Sathyamangalam and Mudumalai Tiger Reserves

Abstract: India, a megabiodiversity nation, is home to 4,800 species and 1.3 billion people. The proximity of people and wildlife produces a wide variety of human-wildlife interactions particularly with forest-dwelling communities embedded deep within protected areas (PAs). We evaluated people-park relationships through the 421 families in Thengumarahada located between Sathyamangalam and Mudumalai Tiger Reserves in India. This settlement was originally granted land rights in 1948 but has been subleased many times over.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…For example, variables that belong to socio-economic category such as respondent age, gender, education, family size, and economic well-being have been known to influence forest resource use and ultimately the nature of interaction with forest and wildlife. Several studies have demonstrated a significant influence of these variables on the attitude toward conservation and reintroduction (Williams et al, 2002;Ericsson and Heberlein, 2003;Meadow et al, 2005;Ogra and Badola, 2008;Badola et al, 2012;Karanth and Ranganathan, 2018;Hiroyasu et al, 2019). Similarly, other studies have shown that the benefits from forest and wildlife can affect the attitude of people toward conservation in a positive manner (Williams et al, 2002;Lindsey et al, 2005;Lamichhane et al, 2018;Talukdar and Gupta, 2018;Sakurai et al, 2020).…”
Section: Variable Selectionmentioning
confidence: 98%
See 3 more Smart Citations
“…For example, variables that belong to socio-economic category such as respondent age, gender, education, family size, and economic well-being have been known to influence forest resource use and ultimately the nature of interaction with forest and wildlife. Several studies have demonstrated a significant influence of these variables on the attitude toward conservation and reintroduction (Williams et al, 2002;Ericsson and Heberlein, 2003;Meadow et al, 2005;Ogra and Badola, 2008;Badola et al, 2012;Karanth and Ranganathan, 2018;Hiroyasu et al, 2019). Similarly, other studies have shown that the benefits from forest and wildlife can affect the attitude of people toward conservation in a positive manner (Williams et al, 2002;Lindsey et al, 2005;Lamichhane et al, 2018;Talukdar and Gupta, 2018;Sakurai et al, 2020).…”
Section: Variable Selectionmentioning
confidence: 98%
“…Structured household questionnaire survey method (Gillingham and Lee, 2003;Bhattacherjee, 2012;Karanth and Ranganathan, 2018) was used to collect information from the households within the village. A pilot study was carried out in May 2019 in one of the villages, where 23 households were surveyed.…”
Section: Household Surveysmentioning
confidence: 99%
See 2 more Smart Citations
“…With the exception of paying tourists, human populations are excluded from entering Bandipur. Damage and destruction of agricultural crops by wildlife, especially elephants and wild boar, is pervasive around Bandipur, and attacks on livestock by leopards and tigers is common in the region (Karanth and Ranganathan, 2018; Karanth et al., 2013). While policies are in place for local communities to file for compensation following incidents of crop and livestock loss, or human injury and death following encounters with wild animals, communities complain that the compensation system is deeply inadequate.…”
Section: The Conservation Geography Of Bandipurmentioning
confidence: 99%